A nationwide assessment of VOC emissions and ozone formation potential from China’s printing industry: a meta-analysis - Zhai, Jian (Frontiers in Environmental Science, 2025)
IntroductionThe printing industry in China, with an annual output value of ¥1.43 trillion, is a significant source of volatile organic compound (VOC) emissions, which are key precursors to ozone formation. However, a comprehensive national-scale assessment linking VOC emissions to ozone formation potential (OFP) across major industrial zones has been lacking.MethodsThis study conducted a meta-analysis of VOC emissions and their OFP from China's printing industry, encompassing data from 14 major cities across three key regions: the Pearl River Delta, Yangtze River Delta, and Bohai Rim. The analysis integrated data on VOC speciation, concentrations, and pollution control technologies through a systematic review and harmonization of existing literature and industry data.ResultsOxygenated Volatile Organic Compounds (OVOCs) dominated the emission profiles, accounting for 44.6%–81.1% of total VOC emissions. Isopropanol and ethyl acetate were identified as the predominant species, contributing 28.7% ± 5.3% and 24.1% ± 4.8% of total VOCs, respectively. Significant regional variations were observed, strongly linked to differences in ink types and printing processes. OFP values exhibited a wide range from 78.5 to 643.5 mg m−3, with Changsha exhibiting the highest OFP, attributable to its prevalent use of gravure printing. Evaluation of pollution control technologies revealed widespread inefficiency, with 68% of enterprises relying on granular activated carbon (GAC), which typically achieves 40%–75% removal efficiency. In contrast, regenerative thermal oxidizers (RTOs) demonstrated superior performance, exceeding 90% efficiency.DiscussionThe findings highlight substantial regional disparities in emission profiles and OFP, driven by varying industrial practices and regulatory environments. The prevalence of inefficient control technologies like GAC underscores a critical gap in current pollution mitigation efforts. To effectively address VOC emissions and ozone formation, we recommend: (a) mandating the use of water-based inks in high-emission processes such as gravure and flexible packaging printing; (b) upgrading to advanced treatment technologies with >80% collection efficiency; and (c) implementing real-time VOC monitoring systems. This study provides a scientific basis for formulating targeted, region-specific VOC control strategies within China's crucial printing industry.